MiR‐152 induces human dental pulp stem cell senescence by inhibiting SIRT7 expression. Issue 8 (31st March 2016) - Gu, Shensheng; Ran, Shujun; Liu, Bin; Liang, Jingping
Abstract : Human dental pulp stem cells (HDPSCs) have potential applications in regenerative medicine. The molecular mechanisms underlying HDPSC senescence are not completely understood. Here, we investigated the significance of miR‐152 in HDPSC senescence. We show that miR‐152 is upregulated during HDPSC senescence and its overexpression in early passaged HDPSCs induced senescence. Sirtuin 7 (SIRT7) was identified as a target of miR‐152. SIRT7 was downregulated in senescent HDPSCs, whereas miR‐152 inhibition upregulated SIRT7 and suppressed the senescent phenotype and SIRT7 overexpression rescued miR‐152‐induced senescence. Our results demonstrate that the miR‐152/SIRT7 axis plays a key role in the regulation of HDPSC senescence and provide a candidate target to improve the functional and therapeutic potential of HDPSCs. Abstract :